Design and Experimental Study of a Biomass Pellet Gasifier Stove with Heat Recovery System for High Efficiency and Low Emission - Kheang, Seangly; Hankhuntod, Pilin; Wesonga, Lillian Noela (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to design and test a gasifier-type biomass stove equipped with a heat exchanger system as an innovative effort to increase thermal efficiency and reduce CO emissions. Methodology: The stove is designed with a special configuration by adding a heat exchanger to the gasifier system. It has dimensions of 700 mm in height, 400 mm in diameter, a combustion chamber height of 300 mm, combustion chamber diameter of 300 mm, an air inlet pipe diameter of 1.5 inches, an exhaust pipe diameter of 3 inches, and a heat exchanger length of 90 cm. Testing was conducted under cold start and hot start conditions, with variations in grate height (250 mm and 300 mm) and air-fuel ratios (0.9, 1.0, and 1.3). Main Findings: The test results showed that the stove with a heat exchanger system was able to increase the average thermal efficiency to 35.76%, higher than the conventional biomass stove of 28.89%. The CO emissions produced ranged from 19 ppm to 51 ppm, depending on the variation of operation. The optimal conditions were obtained at a grate height configuration of 250 mm and an air-fuel ratio of 1.0 which produced the highest efficiency of 38.02% with CO emissions of 42.78 ppm. Novelty/Originality of this study: The integration of a heat exchange system into a gasifier-type biomass stove has been shown to enhance thermal efficiency, significantly reduce CO emissions, and yield an optimal combination of parameters that are rarely addressed in previous studies.